The Effect of Cash Ratio, DER, and ROA on Dividend Policy: Moderation of Company Size (Study on Banking Sub-Sector Companies Listed on the Indonesia Stock Exchange) - Sukma, Widhi Fitria; Hermuningsih, Sri; Maulida, Alfiatul (Jurnal Samudra Ekonomi dan Bisnis, 2026)
The development of the banking subsector in Indonesia is very rapid. This study was conducted to analyze the effect of liquidity, DER, and ROA on dividend policy and the moderation of company size. Quantitative methods were used with a sample of 12 banking subsectors. The sampling technique used a purposive sampling method. The data analysis method is descriptive statistics and uses the classical assumption test, multiple linear regression analysis, hypothesis testing, and MRA test using the SPSS program version 22. The results of the analysis prove that cash position and ROA do not affect dividend policy, while DER does affect dividend policy. Company size is obtained to moderate the effect of ROA and cash position on dividend policy; on the other hand, it is proven that company size does not moderate DER on dividend policy.